APLIKASI PEMBELAJARAN HURUF HIJAIYAH BERBASIS ANDROID - Widya Khafa Nofa; Dewi Anggraini Puspa Hapsari; Dinda Salsabila Putri (Jurnal Ilmiah Teknik, 2023)
Making the Belajar Mengaji application discusses learning hijaiyah letters. This study aims to help parents introduce hijaiyah letters to their children. In addition, it can make it easier for users to understand and learn hijaiyah letter material and its punctuation anywhere and anytime. The Belajar Mengaji application can be used by users to view material in the form of hijaiyah letters and punctuation marks and is equipped with practice questions about hijaiyah letters to hone users' skills, which are also equipped with sound effects.Belajar Mengaji application was created using Android Studio with Java and XML Programming Language. The method used in this study is the SDLC (System Development Life Cycle) method, which consists of planning, analysis, design, manufacture, and implementation, as well as device testing. This application has been successfully created and implemented on an Android smartphone with a minimum layer criterion of 5 inches and the Android 5.1 (Lollipop) operating system, so that it is running as expected.